Containing HIV and AIDS: Creating a readers’ theatre script for professional learning in higher education - van Laren, L.; Pithouse-Morgan, K.; Masinga, L. (South African Journal of Higher Education, 2019)
We worked together to create a readers’ theatre script as a vehicle for learning about using everyday objects to open up conversations in a workshop on HIV and AIDS curriculum integration research in higher education. Through creating the script and a series of interconnected dialogue pieces we uncovered experiences and understandings of productive containment and connections in professional learning in higher education, especially in relation to sensitive areas such as HIV and AIDS. We demonstrate how we composed the readers’ theatre script as a creative analytical practice to gain insights into our learning, while also discovering more about how this arts-based research practice can enhance individual and collaborative meaning making. Through arts-based collaborative self-study research we were able to deepen and extend our learning in a supportive and inventive manner, which fuelled hopefulness and a renewed sense of purpose.